General evaluation method of seismic resistance of residential house under multiple consecutive severe ground motions with high intensity. (2017) - Ogawa, Yudai; Kojima, Kotaro; Takewaki, Izuru
Two severe ground shakings attacked some specific regions in Kumamoto Prefecture in Japan on April 14 and April 16 of 2016 with the seismic intensity 7 (the highest level in Japan Metheorological Agency (JMA) scale, approximately X-XII in Mercalli scale). In the seismic design codes of many countries, it is usually supposed that a building experiences severe earthquake ground shaking with such level once in its working period. In this paper, a general method is proposed on the evaluation of the seismic resistance of damaged residential houses under multiple consecutive severe ground motions with high intensity. The method can be used for the analysis and design of buildings under multiple consecutive severe ground motions. As in the previous paper, the present paper adopts an impulse as a representative of near-fault ground motion and multiple separated impulses are used as the repetition of intensive ground shakings with high seismic intensity. A building collapse scenario (collapse limit in terms of zero restoring force with P-delta effect) under multiple repeated severe ground shakings is provided and an energy balance law is used for the response evaluation. The reliability of the proposed theories is examined through numerical analysis using recorded ground motions.